Move towards Sustainability and Resiliency: From Industry 4.0 to Industry 5.0 - Talebi, Mohammadamin (International journal of industrial engineering and operational research, 2023)
This paper explores the transition from Industry 4.0 to Industry 5.0 and its implications for sustainability and resiliency. The rapid advancements in technology and the rise of automation have revolutionized industries across the globe. However, as we move forward, it is crucial to consider the environmental and social impact of these transformations. This paper analyzes the potential of Industry 5.0 in promoting sustainability and resilience, focusing on key factors such as circular economy, renewable energy integration, and stakeholder engagement. The findings emphasize the need for holistic approaches that combine technological innovation with sustainable practices, enabling a resilient and environmentally conscious future.